Have you “involution” today—Competition psychology scale for college students - Liu, Yisi; Tu, Yanli; Yang, Hao; Gao, Jie; Xu, Yun; Yang, Qiwei (Frontiers in Psychology, 2022)
In order to investigate the competitive psychology of college students in the current context of fierce social competition, this study compiled a competition psychology scale for college students (i.e., Competition Psychology Scale for College Students, CPS-CS). The scale was administered on an online platform to 628 university students in different regions of China. After item analysis, reliability analysis, and validity analysis, a total of 16-item scale was finally formed. CPS-CS contains four dimensions: hypercompetitive attitude, competitive motivation, personal development competitive attitude, and competitive interpersonal relationship. The reliability and validity of CPS-CS developed in this research meet the requirements of psychometrics.